Relations over the cosmetic counter : a space of identification, distance or hostility? - Bok, G.I. (Penerbit Universiti Kebangsaan Malaysia, 2018)
The cosmetic floor is regarded as the centre stage of a department store. Premium beauty brands spread across the sales area in luxuriously designed cosmetic counters, and at the heart of all this glamour are the retail beauty workers. As aesthetic workers, their job is not limited to appearing impeccable; as service workers, too, their routine involves affective and emotional labour as well. However, working on the cosmetic floor is more than just looking good and sounding right. At times, retail beauty workers have to manage hostility that transpires at the very counters that are designed to provide beautiful experiences. The purpose of this article is to describe and explain the working conditions at the cosmetic counters which give rise to this hostility. To do this the research employed biographical research, fieldwork and unstructured interviews methods. The findings of this research reveal alienated relations and hostility on the cosmetic floor and it comes in the form of contradictory social exchanges between customers, retail beauty workers and the cosmetic floor.